Occupation Growth, Skill Prices, and Wage Inequality - Michael Johannes Böhm; Hans-Martin von Gaudecker; Felix Schran (Institute of Labor Economics (IZA), 2019)
This paper studies the relationship between changes in occupational employment, occupational wages, and rising overall wage inequality. Using long-running administrative panel data with detailed occupation codes, we first document that in all occupations, entrants and leavers earn lower wages than stayers. This empirical fact suggests substantial skill selection effects that are negative for growing occupations and positive for shrinking ones. We develop and estimate a model for prices paid per unit of skill in occupations, which incorporates occupation-specific skill accumulation over the career and endogenous switching across many occupations. Our results shed light on two important puzzles in prior literature. First, consistent with leading explanations for occupational employment changes, price and employment growth are positively related. Strong counteracting skill changes along the lines of our new empirical fact explain why occupational wages are unrelated to employment growth. Second, skill prices establish a long-suspected quantitative connection between occupational changes and the surge in wage inequality.
Keywords: J21; J23; J24; J31; 330; skill prices; selection effects; multidimensional skill accumulation; occupational employment and wages; administrative panel data; wage inequality